The determinants of turnover intention among bank employees - Yeo, Chiu Hoon (2018)
The main purpose of this research is to investigate the determinants of turnover intention among bank employees in Kuala Lumpur. Specifically, the objective of this study is to examine the relationships between employee relations, working environment and conditions, compensation and benefit packages, career advancement opportunities with turnover intention. A total of 150 questionnaires were distributed among bank employees in Masjid Jamek area and the researcher was successfully collected 120 questionnaires from the respective respondents. All the data were analyzed by using Statistical Package for Social Science (SPSS) 23.0 versions. Two types of data analysis were used, which are descriptive analysis and inferential analysis. Descriptive analysis is used to study the respondent demographic information’s such as age, gender, highest education level, length of services, and monthly income level, meanwhile, the inferential analysis is used to determine the relationships between independent variables such as employee relations, working environment and conditions, compensation and benefit packages, career advancement opportunities and dependent variable which is turnover intention. The results of the study show that the relationship between turnover intention and employee relations is weak. However, working environment and conditions, compensation and benefit packages, and career advancement opportunities are moderately correlated to the turnover intention among the bank employees in Masjid Jamek area, Kuala Lumpur, Malaysia. Based on the multiple regression analysis, the study found that two independent variables which are working environment and conditions, and compensation and benefit packages have negative and significant relationship with turnover intention.